SMANTUB (anti tuberculosis smartwatch) integrated with spy-TBC: Early strategy for Tuberculosis eradication based on smartwatch and Aiot-Posbindu-PM-TBC (artificial intelligence of things post for infectious Tuberculosis) - Yuwono, Hasto (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Progress in efforts to eradicate TB or Indonesia free from TB 2030 should be continued and appreciated in order to move towards a more advanced and visionary future. There is still no special application to overcome TB cases in Indonesia based on AIoT or the internet). The aim of this research is to provide an idea to eradicated TB throught health also social care with advanced technology also innovation. Methods: This article uses a literature review method and presents an innovative approach for eradicating tuberculosis through the PDCA cycle. The focus is on setting goals for progress and creating strategies to reach them. The research proposes a new innovation, Smantub, combined with technology to decrease TB cases. Findings: The